Method for improving oxidation acid corrosion resistance of steel casting made of ZG06Cr16Ni5Mo material and steel casting

Through chemical composition design and heat treatment process optimization, the problem of insufficient corrosion resistance of ZG06Cr16Ni5Mo cast steel parts in oxidized acid environment is solved, and excellent strength, hardness and wear resistance are achieved, meeting the requirements of industrial equipment.

CN119265490APending Publication Date: 2025-01-07SICHUAN JINLEI CASTING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411327739.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

ZG06Cr16Ni5Mo cast steel parts have poor corrosion resistance in oxidized acid environments such as nitric acid and oxidized acid atmosphere at high temperatures, and cannot meet the requirements of industrial equipment.

Method used

Through chemical composition design and heat treatment process optimization, the Creq and Nieq equivalents are adjusted, and the content of elements such as Cr, Ni, Mo is controlled. The intermediate frequency electric furnace-VOD vacuum refining and smelting process is adopted and the heat treatment process of normalized and secondary tempering is used to reduce carbide formation and expand the formation of carbides. The γ-phase region inhibits the formation of delta ferrite and improves the stability of martensite structure.

Benefits of technology

It significantly improves the strength, hardness, plastic toughness and oxidative acid corrosion resistance of ZG06Cr16Ni5Mo cast steel parts, meets the requirements of industrial equipment and extends the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265490A_ABST
    Figure CN119265490A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving oxidation and acid corrosion resistance of a ZG06Cr16Ni5Mo material steel casting, which comprises the following steps: designing chemical components of the ZG06Cr16Ni5Mo material steel casting as follows: less than or equal to 0.03% of C, 0.35-0.55% of Si, 0.70-0.95% of Mn, less than or equal to 0.025% of P, less than or equal to 0.015% of S, 15.5-16.0% of Cr, 5.5-6.0% of Ni, less than or equal to 0.10% of Mo, less than or equal to 0.15% of Cu, less than or equal to 0.10% of W, less than or equal to 0.03% of V and the balance of Fe, calculating equivalent weights of Creq and Nieq according to the following formula, and ensuring that Creq is less than or equal to 16.8, nieq is equal to Ni + 30C + 0.5 Mn; all the smelting raw materials are subjected to a smelting process and then subjected to heat treatment in a normalizing and secondary tempering process mode. According to the invention, the components of the ZG06Cr16Ni5Mo material, the smelting process and the heat treatment process are reasonably designed, so that the corrosion resistance and the wear resistance of the steel casting made of the material in an oxidizing acid environment such as nitric acid and an oxidizing acid atmosphere at a high temperature are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of casting, and in particular to a method for improving the oxidation acid corrosion resistance of a ZG06Cr16Ni5Mo steel casting. Background Art

[0002] Large blowers, compressors and other equipment used in the production of nitric acid, ammonium nitrate and other industrial fields require the casing and other parts to have excellent strength, hardness, plasticity and wear resistance due to the complex working environment, and also require good corrosion resistance in oxidizing acid environments such as nitric acid to ensure the service life of the equipment. Ferrite, austenite and ferrite-austenite duplex stainless steel, such as 1Cr7Ti, 1Cr18Mn8Ni5Mo and other stainless steel materials, although they have good plasticity and corrosion resistance, their strength, hardness and wear resistance are far lower than martensitic stainless steel, and cannot meet the use requirements of the equipment.

[0003] ZG06Cr16Ni5Mo is a martensitic stainless steel material, which is widely used in turbine components, valve bodies, nuclear power plant pressure vessels and offshore drilling platforms. After proper normalizing and tempering heat treatment, the microstructure of this martensitic stainless steel is tempered martensite and lamellar inversion austenite dispersed in the martensitic matrix and a small amount of delta ferrite phase. After long-term verification, this martensitic stainless steel has good strength and plastic toughness, excellent wear resistance, water erosion resistance, erosion resistance, and good casting and welding properties. However, the corrosion resistance of this stainless steel material is not ideal in oxidizing acid environments such as nitric acid and oxidizing atmospheres at high temperatures.

[0004] In order to meet the use requirements of large-scale blowers, compressors and other equipment in the nitric acid, ammonium nitrate and other industrial fields, the martensitic stainless steel must meet the following requirements: tensile strength (δb) ≥ 760Mpa, yield strength (δs) ≥ 540Mpa, hardness ≥ 235HBW, elongation (A) ≥ 15%, cross-sectional shrinkage (Z) ≥ 35%, room temperature impact energy (AKV2) ≥ 60J, x500 times microstructure is tempered martensite plus no more than 5% δ ferrite; at the same time, it is required to comply with GB / T 4334-2008 Method C (65% nitric acid corrosion test method for stainless steel) for corrosion test (i.e., place the sample in the middle of 65.0±0.2% nitric acid solution, boil it continuously for 48 hours per cycle, use new nitric acid solution for each cycle, take out the test piece after the test, brush off the corrosion products on the surface with a soft brush in running water, wash, dry and weigh the sample, and then calculate the corrosion rate of each sample in each cycle), test for 5 cycles, the maximum value of all samples tested in each cycle shall not exceed 1.75g / (m 2 ·h), the average value of the test results shall not exceed 1.50g / (m 2 h). Summary of the invention

[0005] The purpose of this application is to provide a method and a steel casting of ZG06Cr16Ni5Mo material to improve the corrosion resistance of oxidizing acids, so as to achieve the corrosion resistance and wear resistance of ZG06Cr16Ni5Mo steel casting in an oxidizing acid environment such as nitric acid, and in an oxidizing acid atmosphere at high temperature.

[0006] In order to achieve the above object, the present application provides a method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings, comprising:

[0007] Step 1: Chemical composition design:

[0008] The chemical composition of ZG06Cr16Ni5Mo steel casting is designed as C: ≤0.03%, Si: 0.35-0.55%, Mn: 0.70-0.95%, P: ≤0.025%, S≤0.015%, Cr: 15.5-16.0%, Ni: 5.5-6.0%, Mo: ≤0.10%, Cu: ≤0.15%, W: ≤0.10%, V: ≤0.03%, and the rest is Fe. At the same time, the Creq and Nieq equivalents are calculated according to the following formula to ensure that Creq≤16.8, Nieq≥6.95, Creq=Cr+Mo+1.5Si; Nieq=Ni+30C+0.5Mn;

[0009] Step 2: Smelting process:

[0010] Add scrap steel materials with low carbon, low phosphorus and sulfur content into the medium frequency electric furnace for smelting. After the charge is completely melted, take samples for component analysis. Adjust the composition according to the analysis results. Strictly control the P, S and Cr contents during the medium frequency furnace smelting stage. The tapping temperature is ≥1650℃.

[0011] After the smelting in the medium frequency electric furnace is completed, the molten steel is subjected to VOD refining in the converter, and the C content is strictly controlled. The vacuum degree in the furnace is controlled to below 70pa, and the pressure is maintained for more than 10 minutes. After breaking the vacuum, the temperature is measured and the bag samples are taken to detect the chemical composition. The pouring temperature is 1555-1565℃.

[0012] Step 3: Heat treatment process: normalizing plus secondary tempering is used for heat treatment.

[0013] Preferably, in step 2, when adding charge to the medium frequency electric furnace, small pieces of material are first added to the bottom of the furnace to ensure that the charge is compact, and large pieces of scrap steel and return material are added to the upper part. As the charge in the middle and lower parts of the furnace melt, scrap steel and return material are added successively.

[0014] Preferably, in step 2, after the charge is melted by more than 70%, aluminum wire and calcium silicon wire or calcium silicon-barium wire are added to the molten steel at a rate of 0.5-1 kg / t for deoxidation.

[0015] Preferably, in the step 2, when the molten steel is subjected to VOD refining treatment, the vacuum degree in the furnace is evacuated to below 70 Pa and the pressure is maintained for more than 10 minutes; after breaking the vacuum, the temperature is measured and samples are taken to detect the chemical composition. After the chemical composition is tested to be qualified, pouring is carried out at 1555-1565°C.

[0016] Preferably, in step 3, the normalizing plus secondary tempering heat treatment process is:

[0017] Preferably, the temperature is raised to 1020-1060°C at a rate of 50-80°C / min, and the holding time is calculated based on 1 hour for every 25mm of the maximum thickness of the casting, with a minimum holding time of 8 hours. After the holding time is sufficient, the casting is taken out of the furnace and air-cooled to below 100°C.

[0018] Primary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min, and keep warm for 1h for every 25mm of the maximum thickness of the casting, with a minimum of 8h. After the holding time is sufficient, take the casting out of the furnace and air cool or wind cool to below 100℃;

[0019] Secondary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min. The insulation time is calculated based on 1h for every 25mm of the maximum thickness of the casting, with a minimum insulation time of 8h. After the insulation time is sufficient, air cool or wind cool to below 100℃.

[0020] Preferably, after the casting is heat treated, rough machining, grinding, flaw detection, defect elimination and repair welding are performed.

[0021] Preferably, after the repair welding is qualified, stress relief heat treatment is carried out, and the specific process is: heating to 560-580℃ at a rate of 50-60℃ / min, calculating the insulation time according to the maximum repair welding depth of 1h for every 25mm, and the minimum insulation time is 8h. After the insulation time is sufficient, take out of the furnace and air cool to room temperature.

[0022] Preferably, the casting is heated at a rate of 50-80° C. / min each time during the heat treatment.

[0023] The present application also provides an oxidation-acid corrosion-resistant ZG06Cr16Ni5Mo steel casting, the chemical composition of which is C: ≤0.03%, Si: 0.35% to 0.55%, Mn: 0.70% to 0.95%, P: ≤0.025%, S≤0.015%, Cr: 15.5% to 16.0%, Ni: 5.5% to 6.0%, Mo: ≤0.10%, Cu: ≤0.15%, W: ≤0.10%, V: ≤0.03%, and the rest is Fe;

[0024] Creq≤16.8, Nieq≥6.95,

[0025] Creq=Cr+Mo+1.5Si; Nieq=Ni+30C+0.5Mn.

[0026] The beneficial effects of the present invention are:

[0027] The present invention ensures the excellent strength, hardness, plasticity and toughness of the ZG06Cr16Ni5Mo material casting and good wear resistance and oxidation acid corrosion resistance through component design.

[0028] For stainless steel, Cr is a key element to ensure the corrosion resistance of the material. When Cr forms a solid solution in iron and the mass fraction reaches more than 12.5%, the corrosion rate of stainless steel in nitric acid will be very slow. At the same time, Cr can form an oxide film of Cr2O3 on the surface of steel, passivating the surface of stainless steel and improving corrosion resistance. However, Cr is a strong carbide-forming element and is easy to form chromium carbides (Cr,Fe)23C6 with different electrode potentials from the matrix. If the slow cooling process of heat treatment or improper tempering temperature selection of ZG06Cr16Ni5Mo material is carried out, Cr carbides are easily precipitated on the grain boundaries. These carbides will reduce the toughness of stainless steel and increase its brittleness. At the same time, due to the formation of carbides by Cr, the chromium content in the stainless steel is reduced, resulting in an intergranular "Cr-poor" zone. When the Cr content in the Cr-containing iron-based solid solution is lower than the lower solubility limit, the corrosion resistance of the steel will decrease, and intergranular corrosion will occur. In addition, Cr carbides form micro-batteries due to different matrix potentials, which further deteriorates the corrosion resistance. Therefore, by controlling the C content to 0.03% or less, the carbide content is reduced and the toughness and corrosion resistance of stainless steel are improved. Martensite is a metastable phase formed by austenite through a diffusionless phase transformation. Therefore, in order to obtain a martensitic structure, a basic prerequisite is that an austenite (γ phase) phase region must exist. For the Fe-Cr binary alloy equilibrium phase diagram, when the chromium content is greater than 12%, there is no austenite phase region under all temperature conditions. For this reason, only elements that can expand the γ phase region can be added to achieve the above prerequisite. In terms of the ability to expand the γ phase region, carbon is of course the first, but in order to avoid forming carbides with chromium and reducing corrosion resistance, the carbon content should be as low as possible. Nickel is an austenite-forming element that can expand the γ phase region, austenitize the steel, and adjust the phase transformation point of the steel. Therefore, the carbon content in the steel is reduced and a sufficiently high nickel is added to allow the steel to obtain a martensitic structure. Mn is a relatively soft austenite-forming element and has the function of stabilizing the austenite structure. An appropriate amount of Mn can expand the γ phase region and also improve the plasticity and toughness of stainless steel.

[0029] High chromium and nickel content makes ultra-low carbon martensitic stainless steel have good hardenability, and martensitic structure can be obtained by air cooling. However, when the chromium equivalent is high and the nickel equivalent is low, delta ferrite will appear in the structure. The delta ferrite is distributed in small blocks at the original austenite grain boundaries, and it will form strips when the content is high. Once delta ferrite is generated, it is difficult to eliminate it by heat treatment or reprocessing. Due to the differences in chemical composition, mechanical properties and thermal stability between delta ferrite and martensitic matrix, its appearance has an adverse effect on the performance of steel. It not only reduces the strength of steel, but also affects its large-section performance. In addition, it will become a source of fatigue and abrasion. Ferrite-forming elements (Cr, Mo, Si) will increase the content of delta ferrite, while austenite-forming elements (C, Mn, Ni) will inhibit the appearance of delta ferrite. When the ferrite forming elements (such as Si, Cr, etc.) in the steel are on the upper limit, and the austenite forming elements (such as Ni, etc.) are on the lower limit, it is easy to cause the Ni equivalent (Nieq) margin to be low, and a certain amount of delta ferrite is produced. In order to inhibit the formation and increase of delta ferrite, it is necessary to reasonably design the Cr equivalent (Creq) and Ni (Nieq) equivalent. At the same time, the addition of Mo element will greatly reduce the corrosion resistance of stainless steel in oxidizing acid environment. Therefore, when designing the composition, the Mo content is controlled to be less than 0.1%. The temper brittleness problem that may occur due to low Mo content can be solved by reasonably designing the heat treatment process.

[0030] This application ensures the excellent strength, hardness, plasticity and toughness of ZG06Cr16Ni5Mo castings and good wear resistance and oxidation acid corrosion resistance through chemical composition design.

[0031] The present application uses a heat treatment process to make a small amount of austenite in ZG06Cr16Ni5Mo steel not transformed into martensite when it is cooled to room temperature, and the residual austenite can be transformed into martensite during the first tempering cooling, and a certain amount of reverse austenite can be obtained, so that the strength of the steel is high, but the toughness is low. Adding a second tempering can soften the newly formed martensite, and at the same time increase the stable reverse austenite. The reverse austenite has high thermal stability and is highly dispersed in the martensite matrix, which can significantly improve the toughness of the steel.

[0032] The present application improves the corrosion resistance and wear resistance of ZG06Cr16Ni5Mo steel castings in oxidizing acid environments such as nitric acid and oxidizing acid atmospheres at high temperatures by rationally designing the material composition, smelting process and heat treatment process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a microstructure diagram of the ZG06Cr16Ni5Mo steel casting obtained in Example 1 of the present application, in which the delta ferrite content is less than 2%.

[0034] Figure 2This is the cooling structure transformation diagram of the heat treatment process of Example 1 of the present application. DETAILED DESCRIPTION

[0035] The present invention is described in detail below in conjunction with embodiments.

[0036] Embodiment 1 to Embodiment 3

[0037] A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings, specifically:

[0038] Step 1: Chemical composition design:

[0039] The chemical composition of ZG06Cr16Ni5Mo steel casting is designed as C: ≤0.03%, Si: 0.35-0.55%, Mn: 0.70-0.95%, P: ≤0.025%, S≤0.015%, Cr: 15.5-16.0%, Ni: 5.5-6.0%, Mo: ≤0.10%, Cu: ≤0.15%, W: ≤0.10%, V: ≤0.03%, and the rest is Fe. At the same time, the Creq and Nieq equivalents are calculated according to the following formula to ensure that Creq≤16.8, Nieq≥6.95, Creq=Cr+Mo+1.5Si; Nieq=Ni+30C+0.5Mn;

[0040] Step 2: Smelting process:

[0041] The material is smelted using the medium frequency electric furnace-VOD vacuum refining smelting process. When smelting in the medium frequency electric furnace, select scrap steel materials with low carbon, low phosphorus and sulfur content, first add small materials to the bottom of the furnace to ensure that the charge is compact, and large pieces of scrap steel and return materials are loaded on the top. As the charges in the middle and lower parts of the furnace melt, scrap steel and return materials are added one after another;

[0042] After the charge is melted by more than 70%, aluminum wire and calcium silicon wire or calcium silicon barium are added at a rate of 0.5-1 kg / t of molten steel for deoxidation, and slag-making agent is added to make slag. After the charge is completely melted, samples are taken for component analysis, and the composition is adjusted according to the analysis results. During the medium frequency furnace smelting stage, the P, S and Cr contents are strictly controlled, and the tapping temperature is ≥1650°C. When the molten steel is subjected to VOD refining, the C content is strictly controlled, the vacuum degree in the furnace is controlled to below 70 Pa, and the pressure is maintained for more than 10 minutes. After breaking the vacuum, the temperature is measured and the bag sample is taken to detect the chemical composition. The pouring temperature is 1555-1565°C;

[0043] Step 3: Heat treatment process: normalizing plus secondary tempering is used for heat treatment, as follows:

[0044] Normalizing: Heat up to 1020-1060℃ at a rate of 50-80℃ / min. Calculate the holding time based on 1h for every 25mm of the maximum thickness of the casting. The minimum holding time is 8h. After the holding time is sufficient, take the casting out of the furnace and air cool it to below 100℃.

[0045] Primary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min, and keep warm for 1h for every 25mm of the maximum thickness of the casting, with a minimum of 8h. After the holding time is sufficient, take the casting out of the furnace and air cool or wind cool to below 100℃;

[0046] Secondary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min. The insulation time is calculated based on 1h for every 25mm of the maximum thickness of the casting, with a minimum insulation time of 8h. After the insulation time is sufficient, air cool or wind cool to below 100℃.

[0047] Stress relief heat treatment: heat up to 560-580℃ at a rate of 50-60℃ / min, and calculate the holding time based on 1h for every 25mm of the maximum repair welding depth, with a minimum holding time of 8h. After the holding time is sufficient, take the product out of the furnace and air cool it to room temperature.

[0048] The element detection components of the melt obtained by the smelting process of Examples 1 to 3 are shown in Table 1;

[0049] The heat treatment process control conditions of Example 1 to Example 3 are shown in Table 1;

[0050] The mechanical properties and corrosion test results of the steel castings obtained in Examples 1 to 3 are shown in Table 2.

[0051] Comparative Example 1 to Comparative Example 2

[0052] The difference between Comparative Examples 1 to 2 and Example 1 is that the chemical composition of the ZG06Cr16Ni5Mo steel casting is designed to be C: ≤0.06%, Si: ≤1.00%, Mn: ≤1.00%, P: ≤0.035%, S≤0.030%, Cr: 15.5%~17.5%, Ni: 4.5%~6.0%, Mo: 0.40%~1.00%, Cu: ≤0.50%, W: ≤0.50%, V: ≤0.05%, and the rest is Fe.

[0053] Comparative Examples 1 and 2 are designed by chemical composition, and the elemental composition of the melt is obtained after the smelting process is completed, as shown in Table 1;

[0054] The heat treatment process control conditions of Comparative Example 1 to Comparative Example 2 are detailed in Table 2;

[0055] The mechanical properties and corrosion test results of the steel castings obtained in Comparative Examples 1 and 2 are shown in Table 3.

[0056] Comparative Example 3 to Comparative Example 7

[0057] The difference between Comparative Examples 3 to Comparative Examples 7 and Example 1 is that the heat treatment process control conditions are different from those in Example 1. Specifically, the heat treatment process of Comparative Example 3 is "one normalizing + stress relief heat treatment", the heat treatment process of Comparative Example 4 is "one tempering + stress relief heat treatment", the heat treatment process of Comparative Example 5 is "two tempering + stress relief heat treatment", the heat treatment process of Comparative Example 6 is "one normalizing + one tempering + stress relief heat treatment", and the heat treatment process of Comparative Example 7 is "one normalizing + two tempering".

[0058] Comparative Examples 3 to 7 After the smelting process is completed, the elemental composition of the melt is shown in Table 1;

[0059] The heat treatment process control conditions of Comparative Examples 3 to 7 are detailed in Table 2;

[0060] The mechanical properties and corrosion test results of the steel castings obtained in Comparative Examples 3 to 7 are shown in Table 3.

[0061] The corrosion tests of Examples 1 to 3 and Comparative Examples 1 to 7 were carried out according to GB / T4334-2008 Method C (65% nitric acid corrosion test method for stainless steel, i.e., placing the sample in the middle of a 65.0±0.2% nitric acid solution, boiling it continuously for 48 hours per cycle, using a new nitric acid solution for each cycle, taking out the sample after the test, brushing off the corrosion products on the surface with a soft brush in running water, washing, drying, and weighing the sample, and then calculating the corrosion rate of each sample per cycle). The sample dimensions were length L×width b×thickness a=29.81mm×19.88mm×15.8mm.

[0062] Table 1 Element composition table obtained after the composition design of each embodiment and comparative example through smelting process

[0063]

[0064]

[0065] Table 2 Heat treatment process control conditions for each embodiment and comparative example

[0066]

[0067]

[0068] Table 3 Mechanical properties and corrosion test results of steel castings obtained in various embodiments and comparative examples

[0069]

[0070]

[0071] The ZG06Cr16Ni5Mo steel casting produced by the process scheme of Example 1 has a chemical composition as shown in Table 1, mechanical properties as shown in Table 3, a microstructure of tempered martensite, and a delta ferrite content of less than 2% (see Figure 1 The casting has excellent strength, hardness, elongation and impact toughness. The maximum corrosion rate of the sample is 1.25g / (m 2 h), the average corrosion rate of the sample was 0.92%, and no intergranular corrosion was found. From Table 3, it can be seen that the ZG06Cr16Ni5Mo steel casting produced by the process scheme of the present application has excellent strength, hardness, elongation and impact toughness, and has excellent corrosion resistance.

[0072] By comparing Comparative Examples 1 to 2 with Example 1, it is found that the Creq of Comparative Examples 1 and 2 exceeds 16.8, and the Nieq is less than 6.95. The mechanical properties and corrosion resistance of the obtained steel castings are worse than those of Example 1. The reason is speculated to be that ferrite forming elements (Cr, Mo, Si) will promote the increase of δ ferrite content, while austenite forming elements (C, Mn, Ni) will inhibit the appearance of δ ferrite. When the ferrite forming elements (such as Si, Cr, etc.) in the steel are biased towards the upper limit, and the austenite forming elements (such as Ni, etc.) are biased towards the lower limit, it is easy to cause the Ni equivalent (Nieq) margin to be low, and a certain amount of δ ferrite is produced. Therefore, in order to inhibit the formation and increase of δ ferrite, the present application needs to reasonably design the Cr equivalent (Creq) and Ni (Nieq) equivalent.

[0073] By comparing Comparative Examples 3 to 7 with Example 1, it is found that the mechanical properties and corrosion resistance of the steel castings obtained in Comparative Examples 3 to 7 are worse than those in Example 1. It is speculated that the reason is that the heat treatment process is unreasonable. Example 1 adopts the "normalizing + secondary tempering + stress relief heat treatment" heat treatment process, so that a small amount of austenite does not transform into martensite when the ZG06Cr16Ni5Mo steel is cooled to room temperature. The residual austenite can be transformed into martensite during the first tempering cooling, and a certain amount of reverse austenite can be obtained. The strength of the steel is high, but the toughness is low. Adding the second tempering can soften the newly formed martensite by tempering, and at the same time increase the stable reverse austenite. The reverse austenite has high thermal stability and is highly dispersed in the martensite matrix, which can significantly improve the toughness of the steel. Figure 2 This is the cooling structure transformation diagram of the heat treatment process of Example 1 of the present application.

[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings, characterized in that: include: Step 1: Chemical composition design: The chemical composition of ZG06Cr16Ni5Mo steel casting is designed as C: ≤0.03%, Si: 0.35-0.55%, Mn: 0.70-0.95%, P: ≤0.025%, S≤0.015%, Cr: 15.5-16.0%, Ni: 5.5-6.0%, Mo: ≤0.10%, Cu: ≤0.15%, W: ≤0.10%, V: ≤0.03%, and the rest is Fe, among which Creq≤16.8, Nieq≥6.95, Creq=Cr+Mo+1.5Si; Nieq=Ni+30C+0.5Mn; Step 2: Smelting process: Add scrap steel materials with low carbon, low phosphorus and sulfur content into the medium frequency electric furnace for smelting. After the charge is completely melted, take samples for component analysis. Adjust the composition according to the analysis results. Strictly control the P, S and Cr contents during the medium frequency furnace smelting stage. The tapping temperature is ≥1650℃. After the smelting in the medium frequency electric furnace is completed, the molten steel converter is subjected to VOD refining, and the C content is strictly controlled. The vacuum degree in the furnace is controlled to below 70pa, and the pressure is maintained for more than 10 minutes. After breaking the vacuum, the temperature is measured and the bag sample is taken to test the chemical composition. The pouring temperature is 1555-1565℃; Step 3: Heat treatment process: normalizing plus secondary tempering is used for heat treatment.

2. The method according to claim 1, characterized in that In the step 2, when adding charge to the medium frequency electric furnace, first add small pieces of material to the bottom of the furnace to ensure that the charge is compact, and then add large pieces of scrap steel and return material to the upper part. As the charge in the middle and lower parts of the furnace melts, scrap steel and return material are added one after another.

3. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 1, characterized in that: In the step 2, after the charge is melted by more than 70%, aluminum wire and calcium silicon wire or calcium silicon barium are added to the molten steel at a rate of 0.5-1 kg / t for deoxidation.

4. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 1, characterized in that: In the step 2, when the molten steel is subjected to VOD refining treatment, the vacuum degree in the furnace is evacuated to below 70 Pa and the pressure is maintained for more than 10 minutes; after breaking the vacuum, the temperature is measured and the package samples are taken to detect the chemical composition. After the chemical composition is tested to be qualified, pouring is carried out at 1555-1565°C.

5. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 1, characterized in that: In step 3, the normalizing plus secondary tempering heat treatment process is: Heat up to 1020-1060℃ at a rate of 50-80℃ / min. Calculate the holding time based on 1h for every 25mm of the maximum thickness of the casting. The minimum holding time is 8h. After the holding time is sufficient, take the casting out of the furnace and air cool it to below 100℃. Primary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min, and keep warm for 1h for every 25mm of the maximum thickness of the casting, with a minimum of 8h. After the holding time is sufficient, take the casting out of the furnace and air cool or wind cool to below 100℃; Secondary tempering: heat up to 610-630℃ at a rate of 50-80℃ / min. The insulation time is calculated based on 1h for every 25mm of the maximum thickness of the casting, with a minimum insulation time of 8h. After the insulation time is sufficient, air cool or wind cool to below 100℃.

6. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 1, characterized in that: After the heat treatment process is completed, rough processing, grinding, flaw detection, defect elimination and repair welding are carried out.

7. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 6, characterized in that: After the repair welding is qualified, stress relief heat treatment is carried out, and the specific process is: heating to 560-580℃ at a rate of 50-60℃ / min, calculating the insulation time according to the maximum repair welding depth of 1h for every 25mm, and the minimum insulation time is 8h. After the insulation time is sufficient, take the product out of the furnace and air cool it to room temperature.

8. A method for improving the oxidation acid corrosion resistance of ZG06Cr16Ni5Mo steel castings according to claim 5, characterized in that: During the heat treatment process, the casting is heated at a rate of 50-80°C / min each time.

9. An oxidation acid corrosion resistant ZG06Cr16Ni5Mo steel casting, characterized in that: The chemical composition is C: ≤0.03%, Si: 0.35%~0.55%, Mn: 0.70%~0.95%, P: ≤0.025%, S≤0.015%, Cr: 15.5%~16.0%, Ni: 5.5%~6.0%, Mo: ≤0.10%, Cu: ≤0.15%, W: ≤0.10%, V: ≤0.03%, and the rest is Fe; Among them, Creq≤16.8, Nieq≥6.95, Creq=Cr+Mo+1.5Si; Nieq=Ni+30C+0.5Mn.